Genetic Relatedness and Novel Sequence Types of Non-O157 Shiga Toxin-Producing Escherichia coli Strains Isolated in Argentina - Cadona, Jimena S.; Bustamante, Ana V.; González, Juliana; Sanso, A. Mariel (Frontiers in Cellular and Infection Microbiology, 2016)
Shiga toxin-producing Escherichia coli (STEC) is a foodborne pathogen responsible for severe disease in humans such as hemolytic uremic syndrome (HUS) and cattle, the principal reservoir. Identification of the clones/lineages is important as several characteristics, among them propensity to cause disease varies with STEC phylogenetic origin. At present, we do not know what STEC clones, especially of non-O157:H7, are circulating in Argentina. To fill this knowledge gap we assessed the genetic diversity of STEC strains isolated in Argentina from various sources, mostly cattle and food, using multilocus sequence typing (MLST). Our objectives were to determine the phylogenetic relationships among strains and to compare them with strains from different geographic origins, especially with those from clinical human cases, in order to evaluate their potential health risk. A total of 59 STEC isolates from 41 serotypes were characterized by MLST. Analysis using EcMLST database identified 38 sequence types (ST), 17 (45%) of which were new STs detected in 18 serotypes. Fifteen out of 38 STs identified were grouped into 11 clonal groups (CGs) and, 23 not grouped in any of the defined CGs. Different STs were found in the same serotype. Results highlighted a high degree of phylogenetic heterogeneity among Argentinean strains and they showed that several cattle and food isolates belonged to the same STs that are commonly associated with clinical human cases in several geographical areas. STEC is a significant public health concern. Argentina has the highest incidence of HUS in the world and this study provides the first data about which STEC clones are circulating. Data showed that most of them might pose a serious zoonotic risk and this information is important for developing public health initiatives. However, the actual potential risk will be defined by the virulence profiles, which may differ among isolates belonging to the same ST.